High Rate Water Treatment Plant System: Successful Implementation - ajit, Moh (Teknik Lingkungan Universitas Islam Indonesia, 2010)
The High Rate Water Treatment Plant (HR-WTP) system, which is inexpensive, effective and efficient, hasbeen developed to reduce the common operational problems, and also as an alternative for thedevelopment of water treatment plant systems capacity in Indonesia. HR-WTP-system is superior to thoseof conventional WTP-systems in respect to its capacity, performance, as well as operational liability ofthe system.Mathematical model of the HR-WTP system had been developed and simulation using the mathematicalmodel as well as field observation had been clarified.Implementation of HR-WTP-system in up-rating of the Dekeng-WTP system at PDAM Kota Bogor provedsuccessful in increasing the plant capacity from its original of 500 Lps to more than 1200 Lps. Anothersuccessful application of HR-WTP-system was experienced in the upgrading and up-rating of thePedindang-WTP system at PDAM Kota Pangkalpinang where the plant capacity can be increased fromits original of 50 Lps to 300 Lps. The performance of the WTP-system was also significantly improvedfrom poor performance to very good performance.Keywords: conventional system, filtration rate, high rate system, surface loading